Trends and sources of international taxation - López Espadafor, Carlos María (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
International Tax Law has grown significantly and this has caused a considerable increase in the importance of the legislative production affecting it, through both national and international rules. Within those rules of international origin, conventions intended to avoid international double taxation stand out, essentially those following the OECD model. Along with this and also within European Union law, there has been a significant structuring of the rules involving international taxation. That said, we can never lose sight -upon the basis of the dogmatic structuring of international taxation- of the General International Law rules affecting it. These may occasionally be overshadowed by the rules of the countless international conventions on the matter, but the former rules cannot cease to be taken as the basis. Therefore, the globalized structuring of international taxation cannot ignore the general principles upon which it will be based, either as direct sources in matters of international tax law, or as a sub-discipline within tax law proper. Indeed, the national structuring of international tax law cannot be carried out just by taking into consideration the legislative results of globalization, but also by never losing sight of the principles that lead to general international law tax matters. Even though globalization as a process begins to play a greater role in tax law issues, the country’s national examination of international tax law cannot divert from the general basis of this tax law sub-discipline.